Treatment of cognitive and mood disorders secondary to traumatic brain injury by the association of bilateral occipital nerve stimulation and a combined protocol of multisite repetitive transcranial magnetic stimulation and cognitive training: A case report - Caloc'h, Tiphanie; Le Saout, Estelle; Litaneur, Séverine; Suarez, Alcira; Durand, Sylvain; Lefaucheur, Jean-Pascal; Nguyen, Jean-Paul (Frontiers in Neurology, 2023)
Purpose: Cognitive impairment secondary to traumatic brain injury (TBI) is difficult to treat and usually results in severe disability.Method: A 48-year-old man presented with chronic refractory headaches and persistent disabling cognitive impairment after TBI. He was first treated with occipital nerve stimulation (ONS) implanted bilaterally to relieve headaches (8 years after the head trauma). Two years later, he was treated with a 6-week protocol combining repetitive transcranial magnetic stimulation (rTMS) delivered to multiple cortical sites (prefrontal cortex, language areas and areas involved in visuo-spatial functions) and computerized cognitive training (CogT) (targeting memory, language, and visuo-spatial functions) to improve cognitive performance.Results: Executive and cognitive functions (attention, ability to perform calculations, verbal fluency) improved in association with pain relief after ONS (33-42% improvement) and then improved even more after the rTMS-CogT protocol with an additional improvement of 36-40% on apathy, depression, and anxiety, leading to a significant reduction in caregiver burden. The functional improvement persisted and even increased at 6 months after the end of the rTMS-CogT procedure (10 years after the onset of TBI and 2 years after ONS implantation).Conclusion: This is the first observation describing sustained improvement in post-TBI refractory headache, depression, and cognitive impairment by the association of bilaterally implanted ONS and a combined procedure of multisite rTMS and CogT to target various brain functions.